Ground-based remote sensing of aerosol climatology in China: Aerosol optical properties, direct radiative effect and its parameterization. (January 2016) - Xia, X.; Che, H.; Zhu, J.; Chen, H.; Cong, Z.; Deng, X.; Fan, X.; Fu, Y.; Goloub, P.; Jiang, H.; Liu, Q.; Mai, B.; et al.
Abstract: Spatio-temporal variation of aerosol optical properties and aerosol direct radiative effects (ADRE) are studied based on high quality aerosol data at 21 sunphotometer stations with at least 4-months worth of measurements in China mainland and Hong Kong. A parameterization is proposed to describe the relationship of ADREs to aerosol optical depth at 550 nm (AOD) and single scattering albedo at 550 nm (SSA). In the middle-east and south China, the maximum AOD is always observed in the burning season, indicating a significant contribution of biomass burning to AOD. Dust aerosols contribute to AOD significantly in spring and their influence decreases from the source regions to the downwind regions. The occurrence frequencies of background level AOD (AOD < 0.10) in the middle-east, south and northwest China are very limited (0.4%, 1.3% and 2.8%, respectively). However, it is 15.7% in north China. Atmosphere is pristine in the Tibetan Plateau where 92.0% of AODs are <0.10. Regional mean SSAs at 550 nm are 0.89–0.90, although SSAs show substantial site and season dependence. ADREs at the top and bottom of the atmosphere for solar zenith angle of 60 ± 5° are −16–−37 W m −2 and –66–−111 W m −2, respectively. ADRE efficiency shows slight regional dependence. AOD and SSA together account for more than 94 and 87% of ADRE variability at the bottom and top of the atmosphere. The overall picture of ADRE in China is that aerosols cool the climate system, reduce surface solar radiation and heat the atmosphere. Highlights: A high-quality database of aerosol optical properties in China was established. An empirical relationship of AOD and SSA to ADRE has been introduced. Spatio-temporal variation of aerosol optical properties and ADRE was revealed.